Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pone.0216880
|View full text |Cite|
|
Sign up to set email alerts
|

Recovery of influenza A viruses from lake water and sediments by experimental inoculation

Abstract: Influenza A viruses (IAV) are zoonotic pathogens relevant to human, domestic animal and wildlife health. Many avian IAVs are transmitted among waterfowl via a faecal-oral-route. Therefore, environmental water where waterfowl congregate may play an important role in the ecology and epidemiology of avian IAV. Water and sediment may sustain and transmit virus among individuals or species. It is unclear at what concentrations waterborne viruses are infectious or remain detectable. To address this, we performed lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Though isolation of genetically similar viruses from migratory mallards in successive seasons does not solve the issue of viral persistence and whether that persistence occurs within the waterfowl population or with the added interaction of the environment, it does suggest that IAVs can persist and evolve within a single location over successive seasons, throughout the annual cycle of waterfowl. Many factors, such as water, sediment, and other organisms, have been hypothesized to play a role in maintenance of IAV in the environment and therefore the wild bird population during the overwintering and spring period [ 21 , 37 , 38 , 39 , 40 ]. However, these mechanisms are mostly investigated as in vitro studies performed in the laboratory or are experimental in nature with limited field-based evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Though isolation of genetically similar viruses from migratory mallards in successive seasons does not solve the issue of viral persistence and whether that persistence occurs within the waterfowl population or with the added interaction of the environment, it does suggest that IAVs can persist and evolve within a single location over successive seasons, throughout the annual cycle of waterfowl. Many factors, such as water, sediment, and other organisms, have been hypothesized to play a role in maintenance of IAV in the environment and therefore the wild bird population during the overwintering and spring period [ 21 , 37 , 38 , 39 , 40 ]. However, these mechanisms are mostly investigated as in vitro studies performed in the laboratory or are experimental in nature with limited field-based evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The longest LPAI virus persistence in samples from the environment was observed for water samples, followed by sediment, surfaces, and air [ 113 ]. In addition, LPAI virus cultivation from water samples required minimal viral titres, compared with IAV cultivation from sediment [ 117 ]. Furthermore, mathematical models suggest that environmental reservoirs could play an important role in the ecology of LPAI viruses [ 118 , 119 , 120 , 121 ].…”
Section: Underlying Mechanisms Of Emergence Of Novel Hpai H5 Virusmentioning
confidence: 99%
“…Therefore, various methods have been developed for detecting AIV in water. Several studies have reported methods to detect AIV in surface water during field infections of AIV (12)(13)(14)(15), however, most of these studies only showed the efficiency of their methods under laboratory circumstances (16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%